Coup de'etat the Philippines revolt. (Fall Church, Va. Land Mark Films)
It shows the rebellion of the military with its factions and with the participation of the civil government.
VHS
Keywords: Coups d'etat -- Philippines; Philippines -- History -- Revolution, 1986.; Philippine history; Politics and goverment